PREVALENSI PENDERITA MYOPIA YANG DIREHABILITASI DENGAN LENSA KONTAK LUNAK DI OPTIK KARTIKA JAYA - Arik Kuswoyo; Wahyu Budiana; Ferry Doringin (Akademi Refraksi Optisi dan Optometry Gapopin, 2023)
This study aims to determine the description of the wearer of spherical soft contact lenses as a tool to rehabilitate the visual acuity of patients with myopia refractive error at Kartika Jaya optics Bekasi. The population in this study were all patients with refractive errors who used a soft contact lens vision rehabilitation tool. This type of research is descriptive analytic with a design description of the use of spherical soft contact lenses. The sampling system used in this study is a document research method from the same source, namely all customers who were examined at Kartika Jaya optics. Analysis of hypothesis testing using SPSS version 24, which resulted in: the rehabilitation of visual acuity of patients with refractive errors of myopia using colorless spherical soft contact lenses was quite significant and the use of colored soft toric contact lenses was not significant.